Tying lending and underwriting: Scope economies, incentives, and reputation - Christian Laux; Uwe Walz (Goethe University Frankfurt, Center for Financial Studies (CFS), 2006)
Informational economies of scope between lending and underwriting are a mixed blessing for universal banks. While they can reduce the cost of raising capital for a firm, they also reduce incentives in the underwriting business. We show that tying lending and underwriting helps to overcome this dilemma. First, risky debt in tied deals works as a bond to increase underwriting incentives. Second, with limitations on contracting, tying reduces the underwriting rents as the additional incentives from debt can substitute for monetary incentives. In addition, reducing the yield on the tied debt is a means to pay for the rent in the underwriting business and to transfer informational benefits to the client. Thus, tying is a double edged sword for universal banks. It helps to compete against specialized investment banks, but it can reduce the rent to be earned in investment banking when universal banks compete against each other. We derive several empirical predictions regarding the characteristics of tied deals.
urn:nbn:de:hebis:30-38017
Keywords: G21; G24; D49; 330; Tying; Investment Banking; Universal Banking